The Relationship Between Widal Titer with Platelet and Leukocyte Counts In Typhioid Fever Patients: Hubungan Titer Widal Dengan Jumlah Trombosit dan Leukosit Pada Pasien Demam Tifoid - Mutia Hariani Nurjanah; Anas Fadly Wijaya; Choirul Huda; Chalis Diah Pratiwi (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
Typhoid fever is a systemic infectious disease caused by Salmonella typhi and remains a health problem in developing countries, including Indonesia. The Widal test is still widely used as a supporting diagnostic examination for typhoid fever because it is simple and rapid. Typhoid infection may also cause changes in hematological parameters such as leukocyte and platelet counts. This study aimed to determine the relationship between Widal titers and leukocyte and platelet counts in typhoid fever patients. This study used a quantitative design with a cross-sectional approach. A total of 21 typhoid fever patients were selected using purposive sampling technique. Leukocyte and platelet examinations were performed using the Mindray BC 5300 Hematology Analyzer. Data analysis was conducted using the Shapiro-Wilk normality test followed by Spearman correlation test. The results showed that the correlation between Widal titer and leukocyte count obtained p=0.987 and r=0.004, while the correlation between Widal titer and platelet count obtained p=0.935 and r=0.019. These findings indicate that there was no significant relationship between Widal titer and leukocyte or platelet counts in typhoid fever patients. However, there was a significant relationship between leukocyte and platelet counts with p=0.000 and correlation coefficient r=0.753. In conclusion, Widal titer had no significant relationship with leukocyte and platelet counts in typhoid fever patients, while leukocyte and platelet counts showed a strong positive correlation.